Development of a Quantitative Real-Time PCR Assay for Detection of Toxoplasma gondii in Brain Samples - Mahboubeh Berizi; Jalal Babaie; Pezhman Fard esfahani; Marjan Enshaeieh; Rahmah Noordin; Geita Saadatnia; Majid Golkar (Iranian Journal of Parasitology, 2021)
Background: Toxoplasmosis is a worldwide-distributed infection that can cause serious diseases, mainly in congenitally infected and immunodeficient individuals. PCR assays play an indispensable role in the detection of Toxoplasma gondii in different biological samples.